Research on the Development Path of Sports Industry in the Context of Belt and Road - Liu Ziming, Kharchenko T.О (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the deepening of China's economic transformation and development, sports industry as a new industry is promoting economic growth an indispensable and important force. How to make full use of the opportunity of the times, make use of the new value judgment and standard of the whole society, establish the clear goal of the development of the sports industry, construct the reasonable system, and promote the sports.The rational and orderly development of industry and the backbone of economic development are very worth thinking about. Since 2013,the idea of "Belt and Road" in 2000 makes China's sports industry usher in a new historical opportunity. "Belt and Road" also emphasizes to strengthen the innovation ability open cooperation, forms the sea and land inside and outside linkage, east and west two-way mutual aid open pattern, from then on ," Belt and Road "initiative brings the unprecedented opportunity for our country sports industry development, also faces the huge challenge because of the present world situation complexity.